2009
DOI: 10.1016/j.ejcts.2008.12.054
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function during coronary surgery with and without cardiopulmonary bypass☆

Abstract: Off-pump surgery is associated with thyroid hormone changes similar to conventional surgical revascularisation. The data suggest that further studies into T3 administration during OPCAB may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Cardiopulmonary bypass results in a euthyroid sick syndrome characterized by decreased total and free T3 levels. Interestingly, reduced thyroid levels are not alleviated by opCAB [67]. The influence of additional factors, including urgency of operation, poor left ventricular function, and diabetes, also plays a role in the stress response and should be considered.…”
Section: Discussionmentioning
confidence: 96%
“…Cardiopulmonary bypass results in a euthyroid sick syndrome characterized by decreased total and free T3 levels. Interestingly, reduced thyroid levels are not alleviated by opCAB [67]. The influence of additional factors, including urgency of operation, poor left ventricular function, and diabetes, also plays a role in the stress response and should be considered.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, we wonder if AXC or CPB times are shorter than those in the cases in the article of Velissaris et al (3). If Caluk et al (1) can share the data with us, we may understand well the results that lesser visible of NTIS in their study than other authors’ results.…”
mentioning
confidence: 90%
“…They had analyzed 50–70-year-old patients, while the other authors studied older ones (1). In the article of Velissaris et al (3), they studied the effects of coronary bypass surgery upon thyroid function and compared ONCAB and OPCAB techniques, and found that there was no significant difference between two groups for the changes of thyroid function. They gave us aortic cross clamping (AXC) and CPB time (CPB time=62.6±23.7 min; AXC time=32.6±10.8 min).…”
mentioning
confidence: 99%
“…However, data from patients undergoing cardiac surgery without CPB have demonstrated that the reductions in T3 that have previously been observed in trials of patients undergoing cardiac surgery utilising CPB also occur in the offpump group to a similar magnitude. This implies that the NTIS during cardiac surgery is a non-specific stress response and CPB is not the only contributing factor to its occurrence 46,47 .…”
Section: The Effects Of Cardiopulmonary Bypass On Circulating Levels mentioning
confidence: 99%